1989
DOI: 10.1007/bf01436960
|View full text |Cite
|
Sign up to set email alerts
|

Rydberg states of the K2 molecule studied by laser spectroscopy in a supersonic beam

Abstract: Rydberg states of potassium dimer have been studied in a crossed laser-molecular beam experiment. The K 2 molecules were formed in a supersonic expansion and excited by low-power cw dye laser. Two different excitation schemes have been used: The first scheme uses a single mode ring dye laser to induce near resonant two-photon transitions while in the second scheme stepwise excitation with two dye lasers is used. In each case excitation of Rydberg levels was detected by monitoring the ionization signal resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The RKR potential energy curves calculated using the determined Dunham coefficients are given in Tables II and III. In the absence of theoretical calculations concerning Rydberg states of K 2 (see [22] for the most extensive results) and of direct experimental observations, we can try to assign atomic asymptotes to the observed states only tentatively and by indirect arguments. First, we resort to a general rule that in case of transitions to highly excited molecular states the strongest ones are expected to be those corresponding to the allowed transitions between the asymptotic atomic limits of the molecular states [2,23,24]. Since the observed transitions originate from the ground X 1 Σ + g state, which dissociates to 4s + 4s potassium atoms, it is concluded that the two investigated 1 Π u states correspond to 4s + np and 4s + (n + 1)p asymptotes.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The RKR potential energy curves calculated using the determined Dunham coefficients are given in Tables II and III. In the absence of theoretical calculations concerning Rydberg states of K 2 (see [22] for the most extensive results) and of direct experimental observations, we can try to assign atomic asymptotes to the observed states only tentatively and by indirect arguments. First, we resort to a general rule that in case of transitions to highly excited molecular states the strongest ones are expected to be those corresponding to the allowed transitions between the asymptotic atomic limits of the molecular states [2,23,24]. Since the observed transitions originate from the ground X 1 Σ + g state, which dissociates to 4s + 4s potassium atoms, it is concluded that the two investigated 1 Π u states correspond to 4s + np and 4s + (n + 1)p asymptotes.…”
Section: Results and Analysismentioning
confidence: 99%
“…Most experiments concentrated on states of singlet gerade symmetry, readily accessible via two-step transitions through the well-known intermediate A Π g (4s + nd) to n = 6 [1][2][3][4][5][6][7][8][9] and extrapolation of the longest 1 ∆ g series to n → ∞ provided a reliable value of the molecular ionisation potential [1].…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of reliable theoretical calculations concerning higher excited states of Li 2 we can try to assign (diabatic) atomic asymptotes to the observed states only tentatively. First, we resort to a general rule that in case of transitions to highly excited molecular states the strongest ones are expected to the states corresponding to the allowed transitions between the asymptotic limits of the molecular states [1,2,19]. Since the observed transitions originate from the ground X 1 Σ + g state, which dissociates to 2s+2s lithium atoms, the three excited 1 Π u states investigated in this work correlate most likely to 2s+np asymptotes.…”
Section: Discussionmentioning
confidence: 99%